‘Dead Meat’ Dramas: Diseased Meat and the Public's Health - Waddington, Keir (History compass, 2003)
A series of ‘Dead Meat Drama[s]’ in the 1880s, which culminated in the 1889 Glasgow trial and the appointment of the first royal commission on tuberculosis in 1890, reflected growing contemporary anxiety about food safety.1 Underlying this anxiety was an ongoing concern about the adulteration of common foodstuffs and an emerging bacteriology of food that highlighted the role played by certain food items (mainly meat and milk), not only in cases of poisoning, but, more importantly, in the spread of disease at a time when standards of living and levels of meat consumption were rising. Despite claims by Burnett that by 1900 food no longer represented a significant threat to public health, debates about food safety and its role in the transmission of disease continued to worry the state, veterinarians and medical practitioners.2 Although the public were apathetic about food safety, by the Edwardian period the role food played in spreading certain bacteriological diseases had become an article of faith among public health officials, even if the science was not always with them.